ANALSIS MISKONSEPSI SISWA TERHADAP MATERI SUMBER ENERGI MATA PELAJARAN IPAS KELAS V DI SDN 1 JEBOL MENGGUNAKAN INSTRUMEN DIAGNOSTIK THREE TIER - Hidayatullah, Romadhoni Shiddiqi; Fakhriyah, Fina; Sulistyorini, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The purpose of the study was to analyze the misconceptions experienced by 5th grade students of SDN 1 Jebol on the material of energy sources in science learning, this research method is descriptive quantitative with a diagnostic test method. Data collection was carried out through diagnostic tests on students and finding out the misconceptions experienced by students. The sample in the study was 10 students. This research was conducted at SDN 1 Ngabul in July 2025. The misconception instrument used to measure elementary school students' misconceptions was using a three-tier test format (Three Tier Test). Researchers used an instrument in the form of a test with a level of confidence. The first level is the choice of answers to the questions asked, the second level presents the reasons for choosing the answer. The third level contains the level of confidence in the answer that has been chosen.. The results of the study, it can be concluded that fifth grade students of SDN 1 Jebol still experience misconceptions in several indicators of energy source material in science learning, although the majority are in the category of conceptual understanding and lack of knowledge. The highest level of misconception occurs in indicators related to energy sources based on geographical conditions, while other indicators are in the low misconception category.